2018
DOI: 10.1097/prs.0000000000004499
|View full text |Cite
|
Sign up to set email alerts
|

National Mortality Rates after Outpatient Cosmetic Surgery and Low Rates of Perioperative Deep Vein Thrombosis Screening and Prophylaxis

Abstract: Accreditation agencies provide transparency and insight into outpatient surgical mortality on a national scale. Results suggest that adoption of venous thromboembolism screening techniques may not be universal despite an existing large body of published evidence. Optimization of thromboembolism prevention pathways remains vital, and consideration of anticoagulation in those undergoing abdominoplasty may be important in lowering outpatient mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…28 To reduce mortality, the necessity of early recognition, vigorous fluid resuscitation, and radical surgical débridement has been pointed out by numerous studies. 29 In keeping with previous study, 30 results from our study indicated that VTE events are the identified cause of mortality in patients following body contouring. Consequently, careful documentation of hematoma severity, consistent assessment of VTE risk (ie, Caprini score), and standardized VTE chemoprophylaxis protocols are essential.…”
Section: Discussionsupporting
confidence: 91%
“…28 To reduce mortality, the necessity of early recognition, vigorous fluid resuscitation, and radical surgical débridement has been pointed out by numerous studies. 29 In keeping with previous study, 30 results from our study indicated that VTE events are the identified cause of mortality in patients following body contouring. Consequently, careful documentation of hematoma severity, consistent assessment of VTE risk (ie, Caprini score), and standardized VTE chemoprophylaxis protocols are essential.…”
Section: Discussionsupporting
confidence: 91%
“…[16][17][18] Even though cosmetic surgery patients are often healthy and do not carry multiple risk factors for VTE, it accounts for more deaths among patients undergoing cosmetic surgery than any other cause. 19 In 2012, a task force of the American Society of Plastic Surgeons established guidelines on the assessment and prophylaxis of venous thromboembolism, which is based on the 2005 Caprini risk assessment module. 5,20 However, unknown or undiagnosed disorders as well as gene mutations are not included.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a 2018 white paper issued by the American Association for Accreditation of Ambulatory Surgery Facilities highlighted the importance of venous thromboembolism risk factor assessment for patients undergoing outpatient surgery. 30…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a 2018 white paper issued by the American Association for Accreditation of Ambulatory Surgery Facilities highlighted the importance of venous thromboembolism risk factor assessment for patients undergoing outpatient surgery. 30 Scarce case reports and review literature suggest that the incidence of DVT after forearm, wrist, and hand surgery is very low (LOE: IV, IV, III). [31][32][33] Chemical prophylaxis risks wound complications and likely only provides an improvement in DVT rates for high risk surgical cases.…”
Section: Smentioning
confidence: 99%